Family Resilience and the Prevention of Radicalism: A Maqāṣid al-Sharī‘ah Approach Based on Jasser Auda - Nur Muhammad Saifurrijal; Muhammad Ali Wafa (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – This study analyzes the epistemological construction of maqāṣid al-sharī‘ah in the thought of Jasser Auda and examines its relevance for strengthening family resilience as a preventive framework against contemporary radicalism. It seeks to demonstrate how Auda’s systems-based maqāṣid paradigm can respond to latent, cognitive, and domestic forms of radicalization by reinforcing inclusive and moderate family values. Design/methodology/approach – This research adopts a qualitative library-based method with a descriptive-analytical approach. It critically examines Auda’s principal works on maqāṣid al-sharī‘ah and applies ijtihād maqāṣidī within the framework of uṣūl al-fiqh. The analysis emphasizes systems thinking, multidimensional reasoning, and the developmental orientation of Islamic law in addressing contemporary social challenges. Findings – The study finds that Auda’s reformulation of maqāṣid al-sharī‘ah shifts its orientation from classical ḥifẓ (protection) toward tanmiyah (development) and the realization of human dignity. In the context of family-based radicalism prevention, six interrelated indicators emerge: ḥifẓ al-dīn (balanced and tolerant religiosity), ḥifẓ al-nafs (psychological well-being and rejection of ideological violence), ḥifẓ al-‘aql (critical thinking and digital literacy), ḥifẓ al-nasl (healthy intergenerational relations), ḥifẓ al-māl (economic justice and ethical responsibility), and ḥifẓ al-usrah (family cohesion and moral accountability). Together, these dimensions form a maqāṣidī framework that enhances family resilience and functions as an epistemological safeguard against exclusivism and ideological rigidity. Research limitations/implications – While conceptually integrative, Auda’s maqāṣid framework remains largely normative and requires empirical operationalization. Future research should develop measurable indicators and apply them in family education, policy-making, and community-based prevention programs. Originality/value – This study offers a novel contribution by repositioning maqāṣid al-sharī‘ah as a family-centered preventive framework against radicalism, enriching contemporary Islamic legal discourse with a holistic and context-sensitive perspective.